HAL â HAL YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN - Rio Agung Pramana, 08.05.51.0018; Santoso, Eric (Students Journal of Economic and Management, 2012)
The process of decision-making by consumers in buying products such asgoods or services will be affected by several factors, and to understand the behavior consumers, companies need to understand these factors.The purpose of this study to determine and analyze the effect of price perception, and perception of quality the brand equity to reach a decision on the purchase of spare parts products Bengkel Baru Motor Simongan. The sample in this study of 100 respondents using accidental sampling technique is done by selecting the respondents provided and easy to get the spare parts buyers encountered researchers coincidence in workshops Semarang.Based on the results of this study concluded that partial equity brands, consumer perceptions, and prices have a significant and positive impact on sparepart product purchasing decisions to achieve customer satisfaction dibengkel-workshop Semarang. In a competitive market conditions, customer preference and loyalty is the key to success. Moreover, the current state, the value of a brand which is comparable to the value of the hard reality is created. Marketing today is meeting consumer perceptions, not just meeting the product. Some quality products, models, features (additional characteristics of a product) and the relative quality of each can have different performance inthe market due to differences in perception of the minds of the consumer product. Building a perception can be done through the brand. The famous brand can have brand equity (brand equity) is strong. A product with a strong brand equity can establish brand platform (foundation brand) is strong and capable develop a brand presence in any competition in the long term. With the increasing number of brands on the market; products that have a strong brand equity that will be able to compete, win and dominate the market (Durianto, Sugiarto, Sitinjak, 2001). The suggestions can be submitted that efforts need to be the owner of the workshop in choosing the product can be maximized by considering matters related with increased perceptions of price, perceived quality and brand equity in accordance the desires of consumers and the market. With the best selection of products expected to achieve the business targets Keywords: price perception, perception of quality products, brand equity, and buying decision.